Positive electrode material, positive electrode plate and secondary battery

By using particles with different particle sizes and surface coating modification in the positive electrode material of lithium-ion batteries, the particle size distribution and surface characteristics are optimized, and the problems of poor energy density and circulation performance of lithium-ion batteries are solved, achieving low gas production and long-term Cycling and high stability positive electrode materials improve the electrochemical and safety performance of the battery.

CN119252895APending Publication Date: 2025-01-03SHENZHEN CITY BATTERY NANOMETER TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411377572.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The energy density of existing lithium-ion battery cathode materials is not high, and the circulation performance and stability are poor, resulting in a short range of single charges. The high-nickel cathode materials are prone to side reactions, absorb carbon dioxide and water, affecting battery performance.

Method used

The first and second particles with different particle sizes are mixed and modified, and the positive electrode material is subjected to surface cladding layer to control the particle size distribution, specific surface area and rest angle relationship, reduce the agglomeration of small particles, and improve the dispersion of large particles. and support, optimize the surface energy stability coefficient, and form a cathode material with low gas yield, long circulation and high stability.

Benefits of technology

It improves the electrochemical performance and safety performance of the cathode material, extends the cycle life, reduces gas production, and enhances the storage performance and temperature stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252895A_ABST
    Figure CN119252895A_ABST
Patent Text Reader

Abstract

The invention provides a positive electrode material, a positive electrode plate and a secondary battery. The positive electrode material comprises a base material and a coating, the coating at least partially coats the surface of the base material, the positive electrode material comprises first particles and second particles, the median diameter of the first particles is S1, the median diameter of the second particles is S2, the true median diameter of the positive electrode material is S < = S1 * H + S2 * L, 13 [mu] m < S1 < 20 [mu] m, 3 [mu] m < S2 < 6 [mu] m, 0.65 < = H < 1, 0 < = L < 0.35, and H + L = 1, h and L are the mass percent of the first particles and the mass percent of the second particles in the base material respectively. The first particles and the second particles with different particle sizes are mixed and matched, and the surface of the positive electrode material is coated and modified, so that the surface characteristics of the positive electrode material are optimized, and the positive electrode material with low gas production, long circulation and high stability is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of battery positive electrode materials, and in particular to a positive electrode material, a positive electrode sheet and a secondary battery. Background Art

[0002] Currently, lithium-ion batteries are widely used in the field of new energy vehicles. However, their energy density is not high enough and the driving range of a single charge is short, which cannot meet the needs of the majority of car consumers. Therefore, it is urgent to further improve the energy density of lithium-ion batteries, and the development of positive electrode materials with higher specific energy is the key to improving the energy density of lithium-ion batteries.

[0003] Positive electrode materials, such as nickel-cobalt-manganese ternary positive electrode materials (NCM), have higher discharge capacity and higher energy density, and their production cost is much lower than that of LiCoO2, and have become the focus of current research. However, as the nickel content in the positive electrode material increases, the highly active Ni 4+ Ions are prone to side reactions with the electrolyte, causing battery capacity and cycle performance to decay, and especially producing a large amount of gas, affecting the storage performance of the material; moreover, the surface residual alkali content of high-nickel positive electrode materials is relatively high, and they are easy to absorb carbon dioxide and water to form compounds such as lithium carbonate and lithium hydroxide, thereby consuming lithium in the material, reducing the electrochemical activity of the positive electrode material, and may hinder the diffusion of lithium ions, affecting battery performance; in addition, due to the sudden change of lattice volume during charging and discharging, high-nickel NCM material particles are easily affected by internal stress and produce microcracks, which extend along the interface between the active material and the electrolyte, accelerating particle pulverization and electrolyte decomposition, leading to cycle capacity decay.

[0004] Therefore, it is urgent to develop a new type of modified high-nickel positive electrode material to solve the above problems. Summary of the invention

[0005] In view of this, in order to solve at least one of the above defects, the present application provides a new type of positive electrode material, which has the properties of low gas production, long cycle and high stability.

[0006] In addition, the present application also provides a positive electrode sheet and a secondary battery using the above-mentioned positive electrode material.

[0007] In the first aspect, an embodiment of the present application provides a positive electrode material, which includes a first particle and a second particle. The median particle size of the first particle is S1, the median particle size of the second particle is S2, and the true median particle size of the positive electrode material is S≤S1*H+S2*L, wherein 13μm<S1<20μm, 3μm<S2<6μm, 0.65≤H<1, 0≤L<0.35, and H+L=1, and H and L are respectively the mass percentages of the first particle and the second particle in the matrix material.

[0008] In some possible embodiments, the specific surface area of ​​the positive electrode material is A m 2 / g, the actual median particle size of the positive electrode material is Sμm, the repose angle of the positive electrode material is θ, and the surface energy coefficient of the positive electrode material is K, then the following relationship is satisfied: K=A / S×(0.1×θ-3.5), and 0<K<0.15.

[0009] In some possible embodiments, the positive electrode material includes first particles and second particles, the median particle size of the first particles is S1, the median particle size of the second particles is S2, and the actual median particle size of the positive electrode material is S≤S1*H+S2*L, wherein 13μm<S1<20μm, 3μm<S2<6μm, 0.65≤H≤1, 0≤L≤0.35, and H+L=1, H and L are respectively the mass percentages of the first particles and the second particles in the positive electrode material.

[0010] In some possible embodiments, the positive electrode material includes a first particle and a second particle, the first particle includes a first substrate and a first coating at least partially coated on the surface of the first substrate, the second particle includes a second substrate and a second coating at least partially coated on the surface of the second substrate, the first coating includes a first coating layer and a second coating layer, the first coating layer is coated on at least a portion of the surface of the first substrate, the second coating layer is coated on the surface of the first coating layer or the surface of the first substrate, the second coating includes a third coating layer and a fourth coating layer, the third coating layer is coated on at least a portion of the surface of the second substrate, The fourth coating layer is coated on the surface of the third coating layer or the surface of the second substrate, and the coating element N11 in the first coating layer, the coating element N21 on the second coating layer, the coating element N12 in the third coating layer and the coating element N22 on the fourth coating layer are all selected from one or more elements of Al, Ti, Zr, Nb, W, B, P and S, and the coating element N11 and the coating element N21 are not completely the same, the coating element N12 and the coating element N22 are not completely the same, and the coating element N11 on the first coating layer and the coating element N12 on the third coating layer are not completely the same.

[0011] In some possible embodiments, the general formula of the first particle is as follows: Li a Ni x Co y Mn z M1 b N11 c N21 d O2, the general formula of the second particle is as follows: Li a Ni xCo y Mn z M2 b N12 c N22 d O2, wherein N11 and N12 elements are selected from one or more elements of Al, Ti, Zr, Nb, W, B, P and S, and N11 and N12 are not completely the same, N21 and N22 elements are selected from one or more elements of Al, Ti, Zr, Nb, W, B, P and S, and N21 and N22 are not completely the same, M1 and M2 elements are selected from one or more elements of Al, Ti, Zr, Mg, Sr, Ba, Nb, W, B and Y, etc., and are not completely the same.

[0012] In some possible embodiments, the positive electrode material satisfies at least one of the following characteristics: (1) the specific surface area A is in the range of 0.1 m 2 / g~1.0m 2 / g; (2) the range of the repose angle θ is 35° to 80°; (3) the tap density of the positive electrode material is >2.2g / cm 3 ; (4) The compaction density of the positive electrode material is greater than 3.0 g / cm 3 ; (5) The residual alkali of the positive electrode material LiOH is less than 0.4wt%, Li2CO3 is less than 0.3wt%; (6) The pH of the positive electrode material is less than or equal to 11.80.

[0013] In a second aspect, an embodiment of the present application provides a method for preparing a positive electrode material, comprising the following steps:

[0014] A dopant is added to a mixture of a first hydroxide and a lithium source, and the mixture is mixed and heated to obtain a first matrix, wherein the median particle size D50 of the first matrix satisfies 13 μm<D50<20 μm; the first matrix is ​​mixed and sintered with a first coating agent to obtain a large-particle coated product containing a first coating layer;

[0015] Adding a dopant to a mixture of a second hydroxide and a lithium source and performing a mixed heating treatment to obtain a second matrix, wherein the median particle size D50 of the second matrix satisfies 3 μm<D50<6 μm; mixing the second matrix with a second coating agent and sintering them to obtain a small particle coated product containing a third coating layer; and

[0016] The large-particle coated product containing the first coating layer and the small-particle coated product containing the third coating layer are mixed with the third coating agent and heated to obtain a positive electrode material.

[0017] In a third aspect, an embodiment of the present application provides a positive electrode plate, comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode material as described above.

[0018] In a fourth aspect, an embodiment of the present application provides a secondary battery, comprising a housing, an electrode assembly, and an electrolyte or an electrolyte, wherein the electrode assembly and the electrolyte or the electrolyte are both located within the housing, the electrode assembly comprises a separator and a negative electrode plate, the electrode assembly further comprises a positive electrode plate as described above, and the separator is disposed between the positive electrode plate and the negative electrode plate.

[0019] The embodiment of the present application mixes first particles and second particles of different particle sizes and modifies the surface coating layer of the positive electrode material, thereby reducing the agglomeration of small particles and allowing the small particles to be evenly filled in the gaps of large particles. During the rolling process of the electrode sheet, the small particles are evenly dispersed in the gaps of large particles and can provide good support, thereby reducing the breakage of large particles during the rolling process, thereby obtaining a positive electrode material with low gas production, long cycle and high stability.

[0020] In addition, the embodiment of the present application also controls the surface energy stability coefficient of the positive electrode material to satisfy 0<K<0.15 by constructing a combined relationship between the particle size distribution, specific surface area and repose angle of the positive electrode material. Therefore, the surface characteristics of the positive electrode material matrix are improved by the synergy of the three, thereby effectively improving the stability, cycle life and storage performance of the positive electrode material, and improving the electrochemical performance and safety performance of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a schematic cross-sectional view of a lithium-ion battery using the positive electrode material of an embodiment of the present application during charging.

[0022] Figure 2 It is a schematic cross-sectional view of a lithium-ion battery using the positive electrode material of an embodiment of the present application during discharge.

[0023] Figure 3 This is a scanning electron microscope (SEM) photograph of the positive electrode material of Example 1 of the present application.

[0024] Figure 4 This is the particle size distribution curve of the positive electrode material in Example 1 of the present application.

[0025] Figure 5 This is a SEM photograph of the cross-section of the positive electrode sheet formed using the positive electrode material of Comparative Example 3.

[0026] Figure 6 This is a SEM photograph of a cross-section of a positive electrode sheet prepared from the positive electrode material provided in Example 1 of the present application. DETAILED DESCRIPTION

[0027] The embodiments of the present application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application; it should be noted that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by technicians in the technical field of the present application; in the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other; many specific details are elaborated in the following description to facilitate a full understanding of the present application, and the described embodiments are only part of the embodiments of the present application, not all of the embodiments.

[0028] The current positive electrode materials have poor stability and cycle performance, and high gas production, which seriously affect the electrochemical performance and safety performance of the positive electrode materials. The inventors of this application found in their research that by improving the surface properties of the positive electrode materials, the problems of poor stability, cycle life, and storage performance of the positive electrode materials can be solved to improve the electrochemical performance and safety performance of the positive electrode materials. How to improve the surface properties of the positive electrode materials and to what extent the above-mentioned technical problems can be solved have become the research focus of this application.

[0029] To this end, an embodiment of the present application provides a positive electrode material, which includes a first particle and a second particle, the median particle size of the first particle is S1, the median particle size of the second particle is S2, and the real particle size median S of the positive electrode material is S≤S1*H+S2*L, wherein 13μm<S1<20μm, 3μm<S2<6μm, 0.65≤H<1, 0≤L<0.35, and H+L=1, H and L are the mass percentages of the first particle and the second particle in the matrix material, respectively. Exemplarily, S1 can be 13.1μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 19.9um or a value between any two of the above values, and S2 can be 3.1μm, 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm, 5.9μm or a value between any two of the above values. Illustratively, H may be 0.66, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 0.99 or a value between any two of the above values, and L may be 0, 0.1, 0.15, 0.2, 025, 0.3, 0.34 or a value between any two of the above values.

[0030] This application modifies the surface of the second substrate by coating, so that the coated small-particle second substrate has good dispersibility and reduces the possibility of small particles agglomerating. This application further modifies the surface of the first substrate by coating, and protects the surface of the first substrate, improves the flatness, gaps and high and low undulation structure of the surface of the large particles, so that the small particles will not adhere to the surface of the large particles after mixing, thereby effectively filling the small particles in the gaps of the large particles, so that the small particles are evenly dispersed in the gaps of the large particles during the rolling process of the pole piece, and can provide good support, thereby reducing the risk of particle breakage of the large particles during the rolling process, and improving the cycle performance and storage performance of the positive electrode material after coating. On the other hand, this application performs surface coating treatment on the first substrate and the second substrate, two particles with different surface characteristics, respectively, and combines different mixing ratios of large and small particles to improve the uniformity of particle mixing and reduce the adhesion problem of large and small particles during the mixing process, so that the mixed material has good fluidity, because the lithium ion diffusion path inside the large particle material is longer, while the small particle material is shorter. The uniform dispersion of small particles can form a certain lithium ion diffusion gradient, which is conducive to the uniform distribution and rapid transmission of lithium ions. Since small particle materials have better thermal conductivity, they can quickly disperse heat throughout the battery, while large particle materials have higher heat capacity and can absorb more heat. The uniform dispersion of large and small particles helps to maintain the temperature stability of the battery during the charging and discharging process and improve the safety of the battery. At the same time, it can also further optimize the structural stability of large and small particles during the pole piece rolling process and the material during the charging and discharging process. Therefore, the aforementioned positive electrode material obtained has low gas production, long cycle and high stability.

[0031] Furthermore, by mixing and modifying the base materials with different particle sizes and surface coating, the crystal structure, particle size, particle morphology, etc. of the positive electrode material can be adjusted, thereby effectively improving the particle surface characteristics of the positive electrode material. Thus, the present application also constructs the specific surface area A m of the positive electrode material 2 / g, the median true particle size Sμm, the angle of repose θ and the surface energy coefficient K, so that these parameters characterizing the surface characteristics of the particles satisfy the following relationship K = A / S × (0.1 × θ-3.5), and the surface energy coefficient K is limited to satisfying 0<K<0.15.

[0032] The present application improves the surface energy of the two particle materials by modifying the surfaces of the first particle and the second particle, and combines the different particle sizes, specific surface areas and repose angles of the large and small particles, comprehensively considers the mutual influence relationship between the specific surface area, particle size and repose angle, and exerts the synergistic regulation effect of the respective characteristics of the large and small particles and the related parameters to synergistically improve the surface characteristics of the positive electrode material matrix, thereby effectively improving the stability, cycle life and storage performance of the positive electrode material, and improving the electrochemical performance and safety performance of the positive electrode material.

[0033] Further, in order to obtain a positive electrode material with better comprehensive performance, the mixing ratio of large and small particles in the positive electrode material is further optimized by comprehensively considering the influence of the characteristics of each of the large and small particles on the crystal structure, particle size, and particle morphology of the positive electrode material. Specifically, 0<L≤0.35, 0.65≤H≤1, and H+L=1 are satisfied. In this embodiment, mixing large particles and small particles can give full play to the advantages of large particles and small particles, so as to further improve the stability and cycle performance of the positive electrode material. For example, H can be 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1 or a value between any two of the above values, and L can be 0, 0.1, 0.15, 0.2, 025, 0.3, 0.35 or a value between any two of the above values.

[0034] In order to obtain a better coating effect, the coating on the surface of the substrate material can be a double coating structure. For example, in the first particle, the first particle includes a first substrate and a first coating at least partially coated on the surface of the first substrate, the first coating includes a first coating layer and a second coating layer, the first coating layer is coated on at least part of the surface of the first substrate, and the second coating layer is coated on the surface of the first coating layer or the surface of the first substrate, wherein the coating element N11 in the first coating layer and the coating element N21 in the second coating layer are both selected from one or more elements of Al, Ti, Zr, Nb, W, B, P and S, and the coating element N11 and the coating element N21 are not completely the same. That is, there is at least one different element between element N11 and element N12. For example, when the first coating layer contains only one coating element N11 and the second coating layer contains only one coating element N21, the two coating elements are different; when the first coating layer contains multiple coating elements N11 and the second coating layer contains multiple coating elements N21, the coating element N11 is not completely the same as the coating element N21, and there is at least one different element between the element N11 and the element N21. In the second particle, the second particle includes a second substrate and a second coating at least partially coated on the surface of the second substrate, the second coating includes a third coating layer and a fourth coating layer, the third coating layer is coated on at least part of the surface of the second substrate, and the fourth coating layer is coated on the surface of the third coating layer or the surface of the second substrate, wherein the coating element N12 in the third coating layer and the coating element N22 in the fourth coating layer are both selected from one or more elements of Al, Ti, Zr, Nb, W, B, P and S, and the coating element N12 and the coating element N22 are not completely the same. That is, there is at least one different element between element N12 and element N22. For example, when the third coating layer contains only one coating element N12 and the fourth coating layer contains only one coating element N22, the two coating elements are different; when the third coating layer contains multiple coating elements N12 and the fourth coating layer contains multiple coating elements N22, the coating element N12 is not completely the same as the coating element N22, and there is at least one different element between element N12 and element N22. Compared with a single coating layer, a double coating layer can more effectively optimize the surface properties of the base material, optimize the surface energy of the particles, reduce side reactions between the positive electrode material and the electrolyte, inhibit the dissolution of metal ions in the positive electrode material, and optimize the cycle performance, stability and storage performance of the positive electrode material.

[0035] Specifically, the first coating layer on the first particle includes a coating element N11, and the third coating layer on the second particle includes a coating element N12. The coating element N11 and the coating element N12 are both selected from one or more elements of Al, Ti, Zr, Nb, W, B, P and S, and are not completely the same. The coating elements N11 and N12 used in the first coating layer coated on the two particles can be flexibly selected, and the two are not completely the same, which facilitates the selection of coating elements according to the particle surface characteristics unique to the first particle and the second particle, and is conducive to obtaining excellent coating effects. In addition, the first coating layer on the first particle and the second particle can be formed by separate coating. Separate coating can make the first particle and the second particle more fully coated, and the formed first coating layer is more uniform, which is conducive to further improving the coating effects of the first particle and the second particle.

[0036] In some embodiments, based on the mass of the positive electrode material, the content of the coating element N11 can be 500-5000 ppm, and the content of the coating element N11 can be 500 ppm, 600 ppm, 700 ppm, 800 ppm, 900 ppm, 1000 ppm, 1500 ppm, 2000 ppm, 2500 ppm, 3000 ppm, 3500 ppm, 4000 ppm, 4500 ppm, 5000 ppm or a content value between any two of the above values.

[0037] In some embodiments, based on the mass of the positive electrode material, the content of the coating element N12 can be 500-5000 ppm, and the content of the coating element N12 can be 500 ppm, 600 ppm, 700 ppm, 800 ppm, 900 ppm, 1000 ppm, 1500 ppm, 2000 ppm, 2500 ppm, 3000 ppm, 3500 ppm, 4000 ppm, 4500 ppm, 5000 ppm or a content value between any two of the above values.

[0038] In some embodiments, based on the mass of the positive electrode material, the content of the coating element N21 can be 500-5000ppm, and the content of the coating element N22 can be 500-2000ppm. By regulating the content of the coating element N21 and the coating element N22, the coating effect of the particle surface can be further optimized. The content of the coating element N21 can be 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm, 1500ppm, 2000ppm, 2500ppm, 3000ppm, 3500ppm, 4000ppm, 4500ppm, 5000ppm or a content value between any two values ​​above. The content of the coating element N22 can illustratively be 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm, 1500ppm, 2000ppm, 2500ppm, 3000ppm, 3500ppm, 4000ppm, 4500ppm, 5000ppm or a content value between any two of the above values.

[0039] The positive electrode material is doped with element M, and element M may be one or more elements selected from Al, Ti, Zr, Mg, Sr, Ba, Nb, W, B and Y. By doping the matrix material, the crystal structure of the positive electrode material can be optimized, which can further improve the surface characteristics of the positive electrode material on the one hand, and further improve the structural stability and conductivity of the positive electrode material on the other hand. Specifically, the matrix material comprises first particles (i.e., polycrystalline large particle materials) and second particles (i.e., polycrystalline small particle materials) of different particle sizes, wherein the doping element M1 in the first particle and the doping element M2 in the second particle are both selected from one or more elements selected from Al, Ti, Zr, Mg, Sr, Ba, Nb, W, B and Y, and may not be completely the same. The doping element can be flexibly selected according to the performance requirements of the actual size of the particles.

[0040] After surface coating modification and mixing of large and small particles, the specific surface area of ​​the positive electrode material can be optimized so that the specific surface area A of the positive electrode material is in the range of 0.1m2 / g to 1.0m2 / g, so as to be suitable for the aforementioned combination relationship, thereby obtaining a surface energy coefficient K that meets the requirements.

[0041] After surface coating modification and mixing of large and small particles, the repose angle of the positive electrode material can be optimized so that the repose angle θ of the positive electrode material is in the range of 35° to 80°, so as to be suitable for the aforementioned combination relationship, thereby obtaining a surface energy coefficient K that meets the requirements.

[0042] In some embodiments, based on the mass of the positive electrode material, the doping amount of the doping element M can be 200 to 5000 ppm. By regulating the doping amount of the original M, the electrochemical performance and surface characteristics of the positive electrode material can be further optimized. The doping amount of the doping element M can be 200ppm, 300ppm, 400ppm, 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm, 1500ppm, 2000ppm, 2500ppm, 3000ppm, 3500ppm, 4000ppm, 4500ppm, 5000ppm or a content value between any two values ​​above.

[0043] The tap density of the positive electrode material provided in the present application is greater than 2.2 g / cm 3 After surface coating modification and mixing of large and small particles, the tap density of the positive electrode material is effectively improved, which is beneficial to improving the capacity and cycle performance of the battery. Preferably, the tap density of the positive electrode material is greater than 3.0g / cm 3 , through surface coating modification and mixing of large and small particles, the particle surface characteristics of the positive electrode material can be optimized, the compaction density of the material can be effectively improved, thereby improving the battery capacity and cycle performance.

[0044] After surface coating modification and mixing of large and small particles, the pH of the positive electrode material is ≤11.80, and the alkalinity is reduced, which reduces its sensitivity to environmental factors such as carbon dioxide and water, making it easy to store. At the same time, the residual alkali on the surface of the positive electrode material is reduced. The residual alkali of the positive electrode material is LiOH <0.4wt%, Li2CO3 <0.3wt%, which effectively improves the electrochemical activity of the positive electrode material and ensures the smooth diffusion of lithium ions in the material, thereby improving the battery performance including the positive electrode material of the present application.

[0045] In some embodiments, the first particle has the following general formula: Li a Ni x Co y Mn z M1 b N11 c N21 d O2, the general formula of the second particle is as follows: Li a Ni x Co y Mn z M2 b N12 c N22 dO2, wherein N11 and N12 elements are selected from one or more elements of Al, Ti, Zr, Nb, W, B, P and S, and N11 and N12 are not completely the same, N21 and N22 elements are selected from one or more elements of Al, Ti, Zr, Nb, W, B, P and S, and N21 and N22 are not completely the same, M1 and M2 elements are selected from one or more elements of Al, Ti, Zr, Mg, Sr, Ba, Nb, W, B and Y, and are not completely the same. The preparation method of the above-mentioned positive electrode material specifically comprises the following steps:

[0046] Step 1: Add a dopant to a mixture of a first hydroxide and a lithium source, perform a mixed heating treatment, and obtain a first matrix, wherein the median particle size D50 of the first matrix satisfies 13 μm<D50<20 μm; and sinter the first matrix and a first coating agent to obtain a large-particle coated product containing a first coating layer. That is, a large-particle coated product is prepared.

[0047] Step 1 specifically includes the following steps:

[0048] Step 11, in the first hydroxide precursor (Ni x Co y Mn z A dopant is added to a mixture of (OH)2) and LiOH to obtain a first mixture, and the first mixture is heat-treated to obtain lithium nickel cobalt manganese oxide (Li a Ni x Co y Mn z O2) substrate (ie, the first substrate).

[0049] Specifically, the first hydroxide precursor (Ni x Co y Mn z (OH)2) and LiOH are weighed according to the molar ratio of lithium element to transition metal in the precursor of (1.02-1.1):1, and the mixture is placed in a pure oxygen atmosphere, the furnace pressure is controlled at 8Pa-12Pa, and the temperature is increased to 750°C-800°C at a heating rate of about 2°C / min, and the temperature is kept for 8-12 hours, and the large-particle matrix material is obtained by natural cooling.

[0050] The first hydroxide precursor is a polycrystalline large particle, and the median particle size D50 is: 13 μm<D50<20 μm.

[0051] In some embodiments, the dopant may be at least one of an oxide and a hydroxide of the doping element M1, and the doping element M1 may include a combination of one or more of Al, Ti, Zr, Mg, Sr, Ba, Nb, W, B, Y, etc. In some embodiments, the dopant is added with a content of 200ppm to 5000ppm of the doping element M1.

[0052] Step 12: Mix the first substrate and the first coating agent (N11) and sinter them to obtain a large-particle coated product.

[0053] Specifically, the first substrate and the first coating agent (N11) are evenly mixed, and the mixture is placed in a pure oxygen atmosphere, the furnace pressure is controlled at 8Pa~12Pa, the temperature is increased to 650℃~720℃ at a heating rate of about 2℃ / min, and the mixture is kept warm for 7~10 hours, and the mixture is cooled naturally to obtain a large-particle coated product containing a first coating layer (N11).

[0054] In some embodiments, the first coating agent (N11) is added so that the content of the coating element N11 is 500 ppm to 5000 ppm.

[0055] In some embodiments, the first coating agent (N11) may be at least one of an oxide and a hydroxide of the coating element N11, and the coating element N11 may be a combination of one or more of Al, Ti, Zr, Nb, W, B, P, S, etc. For example, the first coating agent (N11) may be a combination of zirconium oxide and tungsten oxide.

[0056] Step 2: adding a dopant to a mixture of the second hydroxide and the lithium source and performing a mixed heating treatment to obtain a second matrix, wherein the median particle size D50 of the second matrix satisfies 3 μm<D50<6 μm; and mixing the second matrix with a second coating agent and sintering to obtain a small particle coated product containing a third coating layer. That is, preparing a small particle coated product.

[0057] Step 2 specifically includes the following steps:

[0058] Step 21, in the second hydroxide precursor (Ni x Co y Mn z A dopant is added to a mixture of (OH)2) and LiOH to obtain a second mixture, and the second mixture is heat-treated to obtain lithium nickel cobalt manganese oxide (Li a Ni x Co y Mn z O2) substrate (ie, the second substrate).

[0059] Specifically, the second hydroxide precursor (Ni x Coy Mn z (OH)2) and LiOH are weighed according to the molar ratio of lithium element to transition metal in the precursor of (1.02-1.10): 1. After that, the mixture is placed in a pure oxygen atmosphere, the furnace pressure is controlled at 8Pa-12Pa, and the temperature is increased to 750℃-800℃ at a heating rate of about 2℃ / min, and the temperature is kept for 9-12 hours, and the small particle matrix material is obtained by natural cooling.

[0060] In some embodiments, the second hydroxide precursor is polycrystalline small particles, and the median particle size D50 is: 3 μm<D50<6 μm.

[0061] In some embodiments, the dopant may be at least one of an oxide and a hydroxide of a doping element M2, and the doping element M2 may include a combination of one or more of Al, Ti, Zr, Mg, Sr, Ba, Nb, W, B, Y, etc. The M2 element may not be completely the same as the M1 element doped in the aforementioned large particles.

[0062] In some embodiments, the dopant is added with a doping element M2 content of 200 ppm to 5000 ppm.

[0063] Step 22, mixing the second substrate with the second coating agent (N12) and sintering to obtain a small particle coating product.

[0064] Specifically, the second substrate and the second coating agent (N12) are evenly mixed, and the mixture is placed in a pure oxygen atmosphere, the furnace pressure is controlled at 8Pa~12Pa, the temperature is increased to 650℃~720℃ at a heating rate of about 2℃ / min, and the mixture is kept warm for 7~10 hours, and the temperature is naturally cooled to obtain a small particle coating product.

[0065] In some embodiments, the second coating agent (N12) is added at a content of 500ppm to 5000ppm of the coating element N12.

[0066] In some embodiments, the second coating agent (N12) may be at least one of an oxide and a hydroxide of the coating element N12, and the coating element N12 may be a combination of one or more of Al, Ti, Zr, Nb, W, B, P, S, etc. For example, the second coating agent (N12) may be a combination of aluminum oxide and titanium oxide.

[0067] In some embodiments, the first capping agent (N12) is different from the first capping agent (N11) on the large particles.

[0068] Step 3, washing and removing impurities: mixing the large-particle coated product, the small-particle coated product and pure water in proportion to obtain a slurry, and filtering and heat-treating the slurry to obtain a mixture of large and small particles.

[0069] Specifically, the large particle coated product, the small particle coated product and pure water are added into a reactor in a mass ratio of (100-65):(0-35):100, and stirred at a speed of about 500 rpm / min for 8-12 molecules. The slurry is pressed into a plate and frame filter press for side blowing, and nitrogen or PSA protective gas is used for side blowing for 1-2 hours. Then, the filter cake material is placed in a single cone and vacuumed. The temperature is increased to 170-200°C at a heating rate of 3°C / min-6°C / min, and the temperature is kept for 4-6 hours. The mixture is naturally cooled to obtain a mixture of large and small particles after washing and drying.

[0070] Step 4: Mix the large-particle coated product containing the first coating layer and the small-particle coated product containing the third coating layer with the third coating agent and heat them to obtain the positive electrode material, i.e., the second coating.

[0071] The washed and dried large and small particle mixture is mixed with a third coating agent and heat treated to further form a second coating layer and a fourth coating layer on the surface of the large particle coated product and the small particle coated product to obtain the above-mentioned positive electrode material.

[0072] Specifically, the washed and dried large and small particle mixture is fully and evenly mixed with the third coating agent, and the mixture is placed in a pure oxygen atmosphere, the furnace pressure is controlled at about 10Pa, the temperature is increased to 350℃~450℃ at a heating rate of about 2℃ / min, and the mixture is kept warm for 5~10 hours, and the positive electrode material is obtained by natural cooling.

[0073] In some embodiments, the third coating agent is added so that the content of the coating element N2 is 500ppm to 2000ppm.

[0074] In some embodiments, the third coating agent may be at least one of an oxide and a hydroxide of the coating element N2, and the coating element N2 may be a combination of one or more of Al, Ti, Zr, Nb, W, B, P, S, etc. For example, the first coating agent may be a combination of aluminum oxide and titanium oxide. The coating element N1 is not completely the same as the coating element N2.

[0075] Among them, step 1 and step 2 are respectively coated and modified on the first substrate and the second substrate to form a large-particle coated product having a first coating layer and a small-particle coated product having a third coating layer, and the particle size of the large particles and the particle size of the small particles are controlled. Afterwards, step 3 is a water washing process to wash away surface impurities of the large and small particle coated products, so that the surface gaps of the large and small particle coated products will be exposed, and the specific surface will increase after drying. Step 4 is used for a second coating treatment to form a second coating layer on the exposed surface of the large particle part, and a fourth coating layer is formed on the exposed surface of the small particle part, thereby reducing the overall specific surface area of ​​the positive electrode material, thereby optimizing the repose angle.

[0076] An embodiment of the present application also provides a positive electrode sheet using the aforementioned positive electrode material, comprising a positive electrode collector and a positive electrode active material layer disposed on at least one surface of the positive electrode collector, wherein the positive electrode active material layer comprises the aforementioned positive electrode material.

[0077] The positive electrode current collector may be aluminum foil or nickel foil, or any composite current collector disclosed in the prior art, such as but not limited to a current collector formed by combining the aforementioned conductive foil and a polymer substrate.

[0078] The present application also provides a secondary battery (such as a lithium-ion battery, a sodium-ion battery, etc.), including a housing, an electrode assembly and an electrolyte / electrolyte. The electrode assembly and the electrolyte / electrolyte are both located in the housing. The electrode assembly includes a separator, a negative electrode sheet and the positive electrode sheet, and the separator is disposed between the positive electrode sheet and the negative electrode sheet.

[0079] In some embodiments, the outer shell can be a packaging bag encapsulated by a packaging film (such as an aluminum-plastic film), such as a soft-pack battery. In other embodiments, the secondary battery can also be a steel shell battery, an aluminum shell battery, etc.

[0080] In some embodiments, the electrode assembly may be a laminated structure, which is formed by alternately stacking a positive electrode sheet, a separator, and a negative electrode sheet. In other embodiments, the electrode assembly may also be a wound structure, which is formed by stacking a positive electrode sheet, a separator, and a negative electrode sheet in sequence and then winding them.

[0081] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector. The negative electrode current collector may use at least one of copper foil, nickel foil, stainless steel foil, titanium foil or carbon-based current collector, etc., or may be a composite current collector disclosed in any prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil and polymer substrate. The negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials and lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more. The battery provided in the embodiment of the present application has the advantages of high capacity, high initial efficiency, long cycle life, excellent rate performance and low expansion. The battery can be a lithium-ion battery, a sodium-ion battery, a solid electrolyte battery, etc., without limitation herein.

[0082] like Figure 1 and Figure 2 As shown in the figure, they are schematic diagrams of lithium removal and lithium insertion during the charging and discharging process of a lithium-ion battery prepared by using the positive electrode material provided in the embodiment of the present application. Figure 1 As shown in , when a lithium-ion battery is charged, lithium ions are released from the positive electrode and embedded in the negative electrode; Figure 2 As shown, when a lithium-ion battery is discharged, lithium ions are released from the negative electrode and embedded back into the positive electrode.

[0083] The embodiment of the present application optimizes the surface characteristics of the positive electrode material such as particle size distribution, specific surface area and angle of repose by mixing and modifying the large-particle and small-particle matrix materials and surface coating, thereby obtaining a positive electrode material with low gas production, long cycle and high stability. In addition, the embodiment of the present application also controls the surface energy stability coefficient of the positive electrode material to meet 0<K<0.15 by constructing a combined relationship between the particle size distribution, specific surface area and angle of repose of the positive electrode material. Therefore, the surface characteristics of the positive electrode material matrix are improved by the synergy of the three, thereby effectively improving the stability, cycle life and storage performance of the positive electrode material, and improving the electrochemical performance and safety performance of the positive electrode material.

[0084] The scheme of the present application will be explained below in conjunction with the embodiments. Those skilled in the art will understand that the following examples are only used to explain the present application and cannot be construed as limiting the present application. Unless otherwise stated, the reagents, software and instruments not specifically stated in the following embodiments are all conventional commercial products or open source.

[0085] Embodiment 1:

[0086] Step 1, preparation of a large particle coated product having a first coating layer (N11):

[0087] Step 11: a large-particle hydroxide precursor (Ni 0.83 Co 0.11 Mn 0.06 (OH)2) and LiOH were weighed according to the molar ratio of lithium element to transition metal in the precursor of 1.04:1, and then zirconium oxide as a doping agent was added and mixed thoroughly and evenly according to the doping element content of 2500ppm to obtain a first mixture, and the first mixture was placed in a pure oxygen atmosphere, the furnace pressure was controlled at 10Pa, the temperature was increased to 750℃ at a heating rate of 2℃ / min, and the temperature was kept for 9 hours, and the temperature was naturally reduced to obtain Li 1.04 Ni 0.83 Co 0.11 Mn 0.06 O2 large particle matrix material (first matrix).

[0088] Step 12, place the first substrate and the zirconium oxide coating agent with a coating element content of 1500ppm and the tungsten oxide coating agent with a coating element content of 2000ppm in a mixing equipment for thorough and uniform mixing, and place the mixture in a pure oxygen atmosphere, control the furnace pressure at 10Pa, increase the temperature to 650℃ at a heating rate of 2℃ / min, keep warm for 7 hours, and cool naturally to obtain a large-particle coated product with a first coating layer (N11).

[0089] Step 2, preparation of small particle coated product with third coating layer (N12):

[0090] Step 11, a small-particle hydroxide precursor Ni with a particle size of 3.5 μm is prepared. 0.83 Co 0.11 Mn 0.06 (OH)2 and LiOH were weighed according to the molar ratio of lithium element to transition metal in the precursor of 1.04:1, and then zirconium oxide as a doping agent was added and mixed thoroughly and evenly according to the doping element content of 2500ppm to obtain a second mixture, and the second mixture was placed in a pure oxygen atmosphere, the furnace pressure was controlled at 10Pa, the temperature was increased to 730℃ at a heating rate of 2℃ / min, and the temperature was kept for 9 hours, and the temperature was naturally reduced to obtain Li 1.04 Ni 0.83 Co 0.11 Mn 0.06 O2 (second matrix).

[0091] Step 12, place the second substrate and the titanium oxide coating agent with a coating element content of 1500ppm and the aluminum oxide coating agent with a coating element content of 1000ppm in a mixing equipment for thorough and uniform mixing, and place the mixture in a pure oxygen atmosphere, control the furnace pressure at 10Pa, heat up to 650℃ at a heating rate of 2℃ / min, keep warm for 7 hours, and cool naturally to obtain a small particle coated product containing a third coating layer (N12).

[0092] Step 3, washing and removing impurities:

[0093] The large-particle coated product comprising the first coating layer (N11), the small-particle coated product comprising the third coating layer (N12) and pure water in a mass ratio of 80:20:100 are added into a reactor for stirring at a rotation speed of 500 rpm / min for 10 minutes. The slurry is pressed into a plate and frame filter press for side blowing. Nitrogen or PSA protective gas is used for side blowing for 1.5 hours. The filter cake material is then placed in a single cone for vacuum treatment. The temperature is increased to 200°C at a heating rate of 5°C / min, maintained for 4 hours, and naturally cooled to obtain a mixture of large and small particles after washing and drying.

[0094] Step 4, second wrapping:

[0095] The mixture of large and small particles after washing and drying is fully and evenly mixed with the boron oxide coating agent according to the coating element content of 1500ppm, and the mixture is placed in a pure oxygen atmosphere. The furnace pressure is controlled at 10Pa, and the temperature is increased to 350℃ at a heating rate of 2℃ / min. It is kept warm for 5 hours and cooled naturally to obtain a mixture of the first particles and the second particles (i.e., the positive electrode material).

[0096] Example 2

[0097] The difference from Example 1 is that: Step 3, the large particle coated product comprising the first coating layer (N11), the small particle coated product of the third coating layer (N12) and pure water are added to the reactor in a mass ratio of 90:10:100 for stirring at a speed of 500rpm / min, stirring for 10 minutes, the slurry is pressed into a plate-frame filter press for side blowing, and nitrogen or PSA protective gas is used for side blowing for 1.5 hours, and then the filter cake is placed in a single cone for vacuum treatment, and the temperature is increased to 200°C at a heating rate of 5°C / min, and the temperature is kept for 4 hours, and the mixture of large and small particles is obtained after natural cooling, washing and drying. The other steps are basically the same as those in Example 1, please refer to Example 1 for details.

[0098] Example 3

[0099] The difference from Example 1 is that: Step 3, the large particle coated product comprising the first coating layer (N11), the small particle coated product of the third coating layer (N12) and pure water are added to the reactor in a mass ratio of 70:30:100 for stirring at a speed of 500rpm / min, stirring for 10 minutes, the slurry is pressed into a plate-frame filter press for side blowing, and nitrogen or PSA protective gas is used for side blowing for 1.5 hours, and then the filter cake is placed in a single cone for vacuum treatment, and the temperature is increased to 200°C at a heating rate of 5°C / min, and the temperature is kept for 4 hours, and the mixture of large and small particles is obtained after natural cooling, washing and drying. The other steps are basically the same as those in Example 1, please refer to Example 1 for details.

[0100] Example 4

[0101] The difference from Example 1 is that the positive electrode material is added to the reactor according to the mass ratio of 65:35:100, including the large-particle coated product of the first coating (N11), the small-particle coated product of the third coating (N12) and pure water, and stirred at a speed of 500rpm / min for 10 minutes. The slurry is pressed into a plate-frame filter press for side blowing, and nitrogen or PSA protective gas is used for side blowing for 1.5 hours, and then the filter cake is placed in a single cone for vacuum treatment, and the temperature is increased to 200°C at a heating rate of 5°C / min, and the temperature is kept for 4 hours. The mixture of large and small particles is obtained after natural cooling, washing and drying. The other steps are basically the same as those in Example 1, please refer to Example 1 for details.

[0102] Example 5

[0103] The difference from Example 1 is that: Step 3, a large-particle coated product comprising a first coating layer (N11), a small-particle coated product of a third coating layer (N12) and pure water in a mass ratio of 100:0:100 are added to a reactor for stirring at a speed of 500 rpm / min for 10 minutes, the slurry is pressed into a plate and frame filter press for side blowing, and nitrogen or PSA protective gas is used for side blowing for 1.5 hours, and then the filter cake material is placed in a single cone for vacuum treatment, and the temperature is increased to 200°C at a heating rate of 5°C / min, kept warm for 4 hours, and naturally cooled to obtain a purified large-particle coated product after washing and drying.

[0104] In addition, in step 3 of this embodiment, there is no need to add a small particle coated product having a first coating layer (N12). Therefore, step 2 in embodiment 1 is not required. The other steps are basically the same as those in embodiment 1. Please refer to embodiment 1 for details.

[0105] Example 6

[0106] The difference from Example 1 is that in step 1, a large-particle hydroxide precursor Ni with a particle size of 17.5 μm is 0.83 Co 0.11 Mn 0.06 (OH)2 and LiOH were weighed according to the molar ratio of lithium element to transition metal in the precursor of 1.04:1, and then the dopant was added and mixed thoroughly and evenly to obtain a first mixture. The first mixture was placed in a pure oxygen atmosphere, the furnace pressure was controlled at 10Pa, and the temperature was increased to 750℃ at a heating rate of 2℃ / min, kept at this temperature for 9 hours, and cooled naturally to obtain Li 1.04 Ni 0.83 Co 0.11 Mn 0.06 O2 large particle matrix material (first matrix). Other steps are basically the same as those in Example 1, please refer to Example 1 for details.

[0107] Example 7

[0108] The difference from Example 6 is that: Step 3, the large-particle coated product comprising the first coating layer (11), the small-particle coated product of the third coating layer (12) and pure water are added into the reactor in a mass ratio of 100:0:100, and stirred at a speed of 500 rpm / min for 10 minutes. The slurry is pressed into a plate and frame filter press for side blowing, and nitrogen or PSA protective gas is used for side blowing for 1.5 hours. The filter cake is then placed in a single cone and vacuumed. The temperature is increased to 200°C at a heating rate of 5°C / min, kept warm for 4 hours, and cooled naturally to obtain a large-particle coated product containing purification after washing and drying.

[0109] In addition, in step 3 of this embodiment, there is no need to add a small particle coated product having a second coating layer (12). Therefore, step 2 in embodiment 6 is not required. The other steps are basically the same as those in embodiment 6. Please refer to embodiment 6 for details.

[0110] Example 8

[0111] The difference from Example 1 is that in step 1, a large-particle hydroxide precursor Ni with a particle size of 19.5 μm is 0.83 Co 0.11 Mn 0.06 (OH)2 and LiOH were weighed according to the molar ratio of lithium element to transition metal in the precursor of 1.04:1, and then the dopant was added and mixed thoroughly and evenly to obtain a first mixture. The first mixture was placed in a pure oxygen atmosphere, the furnace pressure was controlled at 10Pa, and the temperature was increased to 750℃ at a heating rate of 2℃ / min, kept at this temperature for 9 hours, and cooled naturally to obtain Li 1.04 Ni 0.83 Co 0.11 Mn 0.06 O2 large particle matrix material (first matrix). Other steps are basically the same as those in Example 1, please refer to Example 1 for details.

[0112] Example 9

[0113] The difference from Example 1 is that in step 2, a small-particle hydroxide precursor Ni with a particle size of 5.5 μm is 0.83 Co 0.11 Mn 0.06 (OH)2 and LiOH were weighed according to the molar ratio of lithium element to transition metal in the precursor of 1.04:1, and then zirconium oxide as a doping agent was added and mixed thoroughly and evenly according to the doping element content of 2500ppm to obtain a second mixture, and the second mixture was placed in a pure oxygen atmosphere, the furnace pressure was controlled at 10Pa, and the temperature was increased to 730℃ at a heating rate of 2℃ / min, kept at this temperature for 9 hours, and cooled naturally to obtain Li 1.04 Ni 0.83 Co 0.11 Mn 0.06 O2 large particle matrix material (first matrix). Other steps are basically the same as those in Example 1, please refer to Example 1 for details.

[0114] Example 10

[0115] The difference from Example 1 is that in step 1, a large-particle hydroxide precursor (Ni 0.6 Co 0.1 Mn 0.3(OH)2) and LiOH are weighed according to the molar ratio of lithium element to transition metal in the precursor of 1.04:1, and then zirconium oxide as a doping agent is added and mixed thoroughly and evenly according to the doping element content of 2500ppm to obtain a first mixture, and the first mixture is placed in a pure oxygen atmosphere, the furnace pressure is controlled at 10Pa, and the temperature is increased to 940℃ at a heating rate of 2℃ / min, and the temperature is kept for 9 hours, and the temperature is naturally reduced to obtain Li 1.04 Ni 0.6 Co 0.1 Mn 0.3 O2 large particle matrix material (first matrix).

[0116] In step 2, a small-particle hydroxide precursor Ni with a particle size of 3.5 μm is prepared. 0.6 Co 0.1 Mn 0.3 (OH)2 and LiOH were weighed according to the molar ratio of lithium element to transition metal in the precursor of 1.04:1, and then zirconium oxide as a doping agent was added and mixed thoroughly and evenly according to the doping element content of 2500ppm to obtain a second mixture, and the second mixture was placed in a pure oxygen atmosphere, the furnace pressure was controlled at 10Pa, and the temperature was increased to 930℃ at a heating rate of 2℃ / min, kept at this temperature for 9 hours, and cooled naturally to obtain Li 1.04 Ni 0.6 Co 0.1 Mn 0.3 O2 small particle matrix material (second matrix).

[0117] Embodiment 11

[0118] The difference from Example 1 is that in step 1, a large-particle hydroxide precursor (Ni 0.7 Co 0.1 Mn 0.2 (OH)2) and LiOH are weighed according to the molar ratio of lithium element to transition metal in the precursor of 1.04:1, and then zirconium oxide as a doping agent is added and mixed thoroughly and evenly according to the doping element content of 2500ppm to obtain a first mixture, and the first mixture is placed in a pure oxygen atmosphere, the furnace pressure is controlled at 10Pa, and the temperature is increased to 880℃ at a heating rate of 2℃ / min, and the temperature is kept for 9 hours, and the temperature is naturally reduced to obtain Li 1.04 Ni 0.7 Co 0.1 Mn 0.2 O2 large particle matrix material (first matrix).

[0119] In step 2, a small-particle hydroxide precursor Ni with a particle size of 3.5 μm is prepared. 0.7 Co 0.1 Mn 0.2(OH)2 and LiOH were weighed according to the molar ratio of lithium element to transition metal in the precursor of 1.04:1, and then zirconium oxide as a doping agent was added and mixed thoroughly and evenly according to the doping element content of 2500ppm to obtain a second mixture, and the second mixture was placed in a pure oxygen atmosphere, the furnace pressure was controlled at 10Pa, the temperature was increased to 870℃ at a heating rate of 2℃ / min, and the temperature was kept for 9 hours, and the temperature was naturally reduced to obtain Li 1.04 Ni 0.7 Co 0.1 Mn 0.2 O2 small particle matrix material (second matrix).

[0120] Comparative Example 1

[0121] The difference from Example 1 is that: the large-particle coated product comprising the first coating layer (N11), the small-particle coated product of the first coating layer (N12) and pure water are added to the reactor in a mass ratio of 60:40:100 for stirring at a speed of 500rpm / min for 10 minutes, the slurry is pressed into a plate-frame filter press for side blowing, and nitrogen or PSA protective gas is used for side blowing for 1.5 hours, and then the filter cake is placed in a single cone for vacuum treatment, and the temperature is increased to 200°C at a heating rate of 5°C / min, and the temperature is kept for 4 hours, and the mixture of large and small particles is obtained after natural cooling, washing and drying. The other steps are basically the same as those in Example 1, please refer to Example 1 for details.

[0122] Comparative Example 2

[0123] The difference from Example 1 is that the large-particle coated product comprising the first coating layer (N11), the small-particle coated product of the first coating layer (N12) and pure water are added to the reactor in a mass ratio of 0:100:100 for stirring at a speed of 500rpm / min for 10 minutes, the slurry is pressed into a plate-frame filter press for side blowing, and nitrogen or PSA protective gas is used for side blowing for 1.5 hours, and then the filter cake is placed in a single cone for vacuum treatment, and the temperature is increased to 200°C at a heating rate of 5°C / min, and the temperature is kept for 4 hours. The small-particle coated product is obtained by natural cooling after washing and drying. The other steps are basically the same as those in Example 1, please refer to Example 1 for details.

[0124] Comparative Example 3

[0125] Step 1, preparation of a large particle coated product having a first coating layer (N11):

[0126] In the first step, a large-particle hydroxide precursor Ni with a particle size of 13.5 μm was prepared. 0.83 Co 0.11 Mn 0.06(OH)2 and LiOH were weighed according to the molar ratio of lithium element to transition metal in the precursor of 1.04:1, and then dopants were added to mix them thoroughly and evenly. The mixture was placed in a pure oxygen atmosphere, the furnace pressure was controlled at 10Pa, and the temperature was increased to 750℃ at a heating rate of 2℃ / min, kept at this temperature for 9 hours, and cooled naturally to obtain Li 1.04 Ni 0.83 Co 0.11 Mn 0.06 O2 large particle matrix material.

[0127] In the second step, the large-particle base material, the zirconium oxide coating agent with a coating element content of 1500ppm, and the tungsten oxide coating agent with a coating element content of 2000ppm are placed in a mixing equipment for thorough and uniform mixing, the mixture is placed in a pure oxygen atmosphere, the furnace pressure is controlled at 10Pa, the temperature is increased to 650℃ at a heating rate of 2℃ / min, the temperature is kept for 7 hours, and the temperature is naturally cooled to obtain a large-particle coated product containing the first coating layer (N11).

[0128] Step 2, preparation of small particle coated product with first coating layer (N12):

[0129] In the first step, 3.5 μm small particles of hydroxide precursor Ni 0.83 Co 0.11 Mn 0.06 (OH)2 and LiOH were weighed according to the molar ratio of lithium element to transition metal in the precursor of 1.04:1, and then dopants were added to mix them thoroughly and evenly. The mixture was placed in a pure oxygen atmosphere, the furnace pressure was controlled at 10Pa, and the temperature was increased to 730℃ at a heating rate of 2℃ / min, kept at this temperature for 9 hours, and cooled naturally to obtain Li 1.04 Ni 0.83 Co 0.11 Mn 0.06 O2 small particle matrix material.

[0130] The small particle base material, titanium oxide coating agent with a coating element content of 1500ppm and aluminum oxide coating agent with a coating element content of 1000ppm are placed in a mixing equipment for thorough and uniform mixing, and the mixture is placed in a pure oxygen atmosphere. The furnace pressure is controlled at 10Pa, and the temperature is increased to 650℃ at a heating rate of 2℃ / min. The temperature is kept for 7 hours, and the temperature is naturally cooled to obtain a small particle coated product containing a first coating layer (N12).

[0131] Step 3, washing and removing impurities:

[0132] The large-particle coated product comprising the first coating layer (N11), the small-particle coated product of the first coating (N12) and pure water in a mass ratio of 80:20:100 are added into a reactor for stirring at a rotation speed of 500 rpm / min for 10 minutes. The slurry is pressed into a plate and frame filter press for side blowing. Nitrogen or PSA protective gas is used for side blowing for 1.5 hours. The filter cake material is then placed in a single cone for vacuum treatment. The temperature is increased to 200°C at a heating rate of 5°C / min, kept warm for 4 hours, and naturally cooled to obtain a mixture of large and small particles after washing and drying.

[0133] Step 4, placing the washed and dried large and small particle mixture in a pure oxygen atmosphere, controlling the furnace pressure at 10Pa, heating to 350°C at a heating rate of 2°C / min, keeping the temperature for 5 hours, and cooling naturally to obtain the positive electrode material.

[0134] Test Method

[0135] The following method was used to perform performance tests on the positive electrode materials obtained in the above Examples 1-11 and Comparative Examples 1-3.

[0136] 1. Particle size test

[0137] The method of dry classification of mixed positive electrode materials using the Japanese NPK DXF airflow classifier is as follows: slowly add the powder into the silo, set the cavity pressure, introduce an inert gas atmosphere, and set the particle size D50 of the classification point between 3um-20um according to the needs, so that the classified large-particle positive electrode materials and small-particle positive electrode materials can be obtained. The volume particle size distribution of the large-particle positive electrode materials and the small-particle positive electrode materials is then tested by the Malvern 3000 tester.

[0138] 2. Repose angle test

[0139] The method of measuring the angle of repose using Japan's Hosokawa comprehensive powder tester PT-X is as follows: slowly add the powder from the top of the funnel, and the material leaking from the bottom of the funnel forms an inclination angle of a cone-shaped accumulation on the horizontal plane. Click the angle of repose measurement in the test software to get the measured value of the angle of repose.

[0140] 3. Material surface morphology test: Hitachi S4800 scanning electron microscope was used to observe the surface morphology of the samples.

[0141] 4. Material specific surface area test: The specific surface area of ​​the material is tested using the Microbeam 3020 nitrogen adsorption method.

[0142] 5. Tap density test: Use the American Quantachrome tap density tester DAT-4-220, weigh 50g of sample and place it in a measuring cylinder, place the measuring cylinder on a vibration table, vibrate it 5000 times, read the sample volume, and calculate the material tap density.

[0143] 6. Compaction density test: Use the American Carver 4350 tester, weigh 1g of sample and put it into the mold with a pressure of 3T for 30s. After compaction, test the height and calculate the compaction.

[0144] 7. Residual alkali test: Use Mettler G20 tester, extract the sample with a certain amount of water, filter, titrate the filtrate with hydrochloric acid standard titrant, calculate the hydrochloric acid consumption and calculate the residual carbonate and hydroxide content of the sample.

[0145] 9. Test of pH value of positive electrode material: Use Mettler FE28, take about 5g of positive electrode material sample, add 45mL of water, ultrasonicate for 5min, take it out and let it stand for 10min. After the pH meter is calibrated, insert the composite electrode into the upper clear liquid to be tested. Calculate the pH value of the solution based on the potential difference between the measuring electrode and the reference electrode.

[0146] 5. Electrochemical cycle performance test

[0147] The electrochemical cycle performance of the positive electrode material was tested by the following method: the positive electrode materials of the above-mentioned Examples 1-9 and Comparative Examples 1-3 were used as positive electrode active materials and mixed with conductive carbon black and binder PVDF (polyvinylidene fluoride) in a mass ratio of 96:2:2, and then NMP (N-methylpyrrolidone) was added to form a uniform slurry and applied on a copper foil, dried in an oven, and rolled at a pressure of 10Mpa, and then cut into a circular positive electrode sheet with a diameter of 14mm. The lithium-ion battery was assembled according to the CR2025 button battery in industry, the diaphragm was Cellgard diaphragm, the electrolyte was a 1mol / L LiPF6 solution with a solvent of EC / PC / DEC, and the negative electrode was a lithium sheet. The entire assembly process was assembled in a glove box filled with argon, and the oxygen content and moisture content in the glove box were controlled below 0.5ppm. The test conditions for lithium-ion batteries are: temperature of 25°C ± 1°C, voltage range of charge and discharge cycle of 3.0V-4.3V, current of 0.1C (210mAh / g), and the cycle test is carried out at 0.5C charge and 1C discharge for 50 weeks.

[0148] 6. Gas production performance test

[0149] The gas generation performance of the positive electrode material was tested by the following method: the positive electrode materials of the above-mentioned Examples 1-9 and Comparative Examples 1-3 were mixed with conductive carbon black and binder PVDF (polyvinylidene fluoride) in a mass ratio of 96.0:1.5:1.5, N-methylpyrrolidone (NMP) was added, and the mixture was stirred evenly in a vacuum stirrer to obtain a positive electrode slurry with a designed surface density of 300 g / m 2 ~400g / m 2, the positive electrode slurry is evenly coated on aluminum foil (thickness of 16 μm), and the coated electrode is dried in an oven at 100°C to 130°C, cold pressed, and cut to obtain the positive electrode. The negative electrode active material graphite, binder (sodium carboxymethyl cellulose + styrene butadiene rubber), and conductive agent acetylene black are evenly mixed in a mass ratio of 96:3:1, deionized water is added, and a vacuum mixer is used to prepare the negative electrode slurry, with a designed surface density of 200 g / m 2 ~300g / m 2 , the mixed slurry is evenly coated on the copper foil (thickness of 8μm), the copper foil is dried at room temperature and then transferred to a 120℃ oven for drying for 1h, the reverse side of the pole piece is treated with the same process, and then the negative pole piece is obtained by cold pressing and slitting. The electrolyte model is TC-E8630J, and the diaphragm is a polypropylene isolation film with a thickness of 16μm. The slit pole pieces are stacked in the order of negative electrode, diaphragm, and positive electrode to make a laminated battery cell, the stacked battery cell is welded through the pole ears, and the welded battery cell is placed in the aluminum-plastic film after punching the pit for packaging, and the electrolyte is injected into the packaged battery cell and sealed to obtain a finished small soft pack battery. After the battery is fully charged to 4.2V at 1C, it is left to stand in a constant temperature box at 80℃ for 3 / 6 / 9 days. The initial volume of the battery and the volume after standing for 3 / 6 / 9 days are determined by the drainage method to obtain the gas production of the battery.

[0150] The corresponding test results of the positive electrode materials of Examples 1-9 and Comparative Examples 1-3 are shown in Tables 1 and 2 below.

[0151] Table 1

[0152]

[0153] Table 2

[0154] Cycle retention rate at 45℃ for 150 cycles <![CDATA[Gas production (cm 3 / Ah) after storage at 80°C for 15 days]]> Example 1 95.2 0.315 Example 2 95.7 0.295 Example 3 94.0 0.356 Example 4 93.3 0.372 Example 5 95.5 0.328 Example 6 95.8 0.308 Example 7 95.6 0.321 Example 8 95.9 0.304 Example 9 95.6 0.311 Example 10 97.5 0.263 Embodiment 11 96.7 0.278 Comparative Example 1 92.8 0.403 Comparative Example 2 91.0 0.482 Comparative Example 3 93.0 0.421

[0155] It can be seen from Table 1 that the specific surface area A, true particle size median S, repose angle θ and surface energy coefficient K of the positive electrode materials in Examples 1-11 satisfy K=A / S×(0.1×θ-3.5), and 0<K<0.15. Combined with the performance test results in Table 2, it can be seen that the cycle retention rate of the positive electrode materials in Examples 1-9 is relatively high, all above 93.3%, and the highest is close to 96%, which is significantly higher than the cycle retention rate of Comparative Examples 1-3. The gas production of the positive electrode materials in Examples 1-9 is relatively low, all at 0.356cm 3 / Ah, the minimum gas output can reach 0.3cm 3 / Ah or less, which is significantly reduced compared with comparative examples 1-3. From the results of Table 1 and Table 2, it can be seen that in Examples 1-9 of the present application, the crystal structure, particle size, morphology, etc. of the positive electrode material can be adjusted by mixing and matching large and small particles and surface modification, and the surface properties of the positive electrode material matrix can be improved. By constructing a combined relationship between the particle size distribution, specific surface area and repose angle of the positive electrode material, the surface properties of the positive electrode material matrix are improved through the synergy of the three, thereby effectively improving the stability, cycle life and storage performance of the positive electrode material, and improving the electrochemical performance and safety performance of the positive electrode material.

[0156] Figure 3 The SEM photo of the positive electrode material of Example 1 is given. Figure 1 It can be seen that the large particles are evenly dispersed with good surface morphology, and the small particles have almost no agglomeration. They are evenly dispersed and filled in the gaps between the large particles, providing good support for the large particles.

[0157] Figure 4 The particle size distribution curve of the positive electrode material of Example 1 is given, and it can be seen that the curve has two peaks, wherein the first peak is the peak corresponding to the first particle, the particle size is in the range of 13μm to 20μm, and the volume share is in the range of 65% to 100%, and the second peak is the peak corresponding to the second particle, the particle size is in the range of 3μm to 6μm, and the volume share is in the range of 0 to 35%, indicating that the positive electrode material in the present application is composed of a mix of two particles with different particle sizes.

[0158] Figure 5 This is a cross-sectional SEM photograph of a positive electrode sheet formed by the positive electrode material prepared in Comparative Example 3. Figure 5 It can be seen that in the positive electrode material of Comparative Example 3, the large particles and the small particles are only coated with one coating layer, and the particle dispersion is poor, resulting in the aggregation of large particles and small particles. During the rolling process of the pole piece, the large particles are damaged and cracked due to mutual collision and extrusion. Combined with Table 2, it can be seen that when the positive electrode material of Comparative Example 3 is applied to the battery, the material cycle becomes worse, the impedance increases, and the gas production is more during the long cycle of the battery.

[0159] Figure 6 This is a cross-sectional SEM photo of a positive electrode sheet prepared from the positive electrode material of Example 1 of the present application, Figure 6 It can be seen that the surface properties of the material can be effectively controlled by modifying the large particles and the small particles respectively, and the dispersion of the large particles and the small particles after mixing is good, there is no agglomeration of the large and small particles themselves, and the small particles can be evenly dispersed in the gaps between the large particles, thereby avoiding direct mutual collision and extrusion between the large particles during the rolling process of the electrode sheet, and can effectively reduce the breakage and cracking of the large particles. Therefore, combined with Table 2, it can be seen that the application of this positive electrode material also exhibits better electrical performance at the battery end.

[0160] The above results show that by mixing and matching large and small particle base materials and performing surface coating modification, the crystal structure, particle size, morphology, etc. of the positive electrode material can be effectively adjusted to improve the surface properties of the positive electrode material base, and a positive electrode material with low gas production, long cycle and high stability can be obtained, which effectively improves the electrochemical performance and safety performance of the positive electrode material. In addition, the embodiment of the present application constructs the specific surface area A m of the positive electrode material 2 / g, the true median particle size Sμm, the repose angle θ and the surface energy coefficient K satisfy the following relationship: K=A / S×(0.1×θ-3.5), and 0<K<0.15. By judging whether the surface energy coefficient K is within the above range of 0 to 0.15, the required positive electrode material with low gas generation, long cycle and high stability can be obtained.

[0161] The above implementation modes are only used to illustrate the technical solutions of the present application and are not intended to limit the present application. Although the present application has been described in detail with reference to the above preferred implementation modes, a person skilled in the art should understand that the technical solutions of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present application.

Claims

1. A positive electrode material, characterized in that: The positive electrode material includes first particles and second particles, the median particle size of the first particles is S1, the median particle size of the second particles is S2, and the true median particle size of the positive electrode material is S≤S1*H+S2*L, wherein 13μm<S1<20μm, 3μm<S2<6μm, 0.65≤H<1, 0<L≤0.35, and H+L=1, H and L are respectively the mass percentages of the first particles and the second particles in the positive electrode material.

2. A positive electrode material, characterized in that: The specific surface area of ​​the positive electrode material is A m 2 / g, the repose angle of the positive electrode material is θ, the surface energy coefficient of the positive electrode material is K, and the positive electrode material satisfies the following relationship K=A / S×(0.1×θ-3.5), and 0<K<0.

15.

3. The positive electrode material according to claim 2, characterized in that The specific surface area A is in the range of 0.1 m 2 / g~1.0m 2 / g; and / or, The range of the repose angle θ is 35° to 80°.

4. The positive electrode material according to claim 2, characterized in that The positive electrode material includes first particles and second particles, the median particle size of the first particles is S1, the median particle size of the second particles is S2, and the true median particle size of the positive electrode material is S≤S1*H+S2*L, wherein 13μm<S1<20μm, 3μm<S2<6μm, 0.65≤H≤1, 0≤L≤0.35, and H+L=1, H and L are respectively the mass percentages of the first particles and the second particles in the positive electrode material.

5. The positive electrode material according to any one of claims 1 to 4, characterized in that The positive electrode material includes a first particle and a second particle, the first particle includes a first substrate and a first coating at least partially coated on the surface of the first substrate, the second particle includes a second substrate and a second coating at least partially coated on the surface of the second substrate, the first coating includes a first coating layer and a second coating layer, the first coating layer is coated on at least a portion of the surface of the first substrate, the second coating layer is coated on the surface of the first coating layer or the surface of the first substrate, the second coating includes a third coating layer and a fourth coating layer, the third coating layer is coated on at least a portion of the surface of the second substrate, the fourth coating layer is coated on the surface of the first coating layer or the surface of the first substrate, The coating layer is coated on the surface of the third coating layer or the surface of the second substrate, and the coating element N11 in the first coating layer, the coating element N21 on the second coating layer, the coating element N12 in the third coating layer and the coating element N22 on the fourth coating layer are all selected from one or more elements of Al, Ti, Zr, Nb, W, B, P and S, and the coating element N11 and the coating element N21 are not completely the same, the coating element N12 and the coating element N22 are not completely the same, and the coating element N11 on the first coating layer and the coating element N12 on the third coating layer are not completely the same.

6. The positive electrode material according to any one of claims 1 to 4, characterized in that The general formula of the first particle is as follows: Li a Ni x Co y Mn z M1 b N11 c N21 d O2, the general formula of the second particle is as follows: Li a Ni x Co y Mn z M2 b N12 c N22 d O2, wherein N11 and N12 elements are selected from one or more elements of Al, Ti, Zr, Nb, W, B, P and S, and N11 and N12 are not completely the same, N21 and N22 elements are selected from one or more elements of Al, Ti, Zr, Nb, W, B, P and S, and N21 and N22 are not completely the same, M1 and M2 elements are selected from one or more elements of Al, Ti, Zr, Mg, Sr, Ba, Nb, W, B and Y, etc., and are not completely the same.

7. The positive electrode material according to any one of claims 1 to 4, characterized in that The positive electrode material satisfies at least one of the following characteristics: (1) The tap density of the positive electrode material is greater than 2.2 g / cm 3 ; (2) The compaction density of the positive electrode material is greater than 3.0 g / cm 3 ; (3) The residual alkali of the positive electrode material LiOH < 0.4wt%, Li2CO3 < 0.3wt%; (4) The pH of the positive electrode material is ≤11.

80.

8. A method for preparing a positive electrode material, characterized in that: The following steps are involved: A dopant is added to a mixture of a first hydroxide and a lithium source, and the mixture is mixed and heated to obtain a first matrix, wherein the median particle size D50 of the first matrix satisfies 13 μm<D50<20 μm; the first matrix is ​​mixed and sintered with a first coating agent to obtain a large-particle coated product containing a first coating layer; Adding a dopant to a mixture of a second hydroxide and a lithium source and performing a mixed heating treatment to obtain a second matrix, wherein the median particle size D50 of the second matrix satisfies 3 μm<D50<6 μm; mixing the second matrix with a second coating agent and sintering them to obtain a small particle coated product containing a third coating layer; as well as The large-particle coated product containing the first coating layer and the small-particle coated product containing the third coating layer are mixed with the third coating agent and heated to obtain a positive electrode material.

9. A positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, characterized in that: The positive electrode active material layer includes the positive electrode material according to any one of claims 1 to 7.

10. A secondary battery, comprising a housing, an electrode assembly, and an electrolyte or an electrolyte, wherein the electrode assembly and the electrolyte or the electrolyte are both located in the housing, and the electrode assembly comprises a separator and a negative electrode sheet, characterized in that: The electrode assembly further comprises the positive electrode sheet as claimed in claim 9, and the separator is disposed between the positive electrode sheet and the negative electrode sheet.